Pengaruh Inflasi, dan Suku Bunga terhadap Indeks Harga Saham Gabungan (IHSG) di Bursa Efek Indonesia (BEI) Periode 2015-2017 - Vivi Melinia Sari; Muhammad Choiru Ramadani; Yoga Edi Setiawan; Misfi Laili Rohmi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study is to examine how interest rates and inflation affect the movement of the Indonesia Stock Exchange's Composite Stock Price Index (IHSG) (BEI). An econometric technique was utilized to do regression analysis on monthly data spanning the years 2015-2017. The study's findings demonstrate how the interest rate variable and the composite stock price index (IHSG) are influenced by the inflation variable, represented as variable X1.